148k views
0 votes
Simplify using exponent rules:3^3×3^4/3^10

1 Answer

2 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{3^3 \cdot 3^4}{3^(10)}\implies \cfrac{3^3 \cdot 3^4\cdot 3^(-10)}{1}\implies 3^(3+4-10)\implies 3^(-3)\implies \cfrac{1}{3^3}\implies \cfrac{1}{27}

User Mahima Agrawal
by
5.0k points